Perbaikan Tanah inceptisol Karawang oleh Cacing (Lumbricus rubellus) dan Mulsa organic serta Kajian Potensi terjadi Erosi Alibatnya - Briljan Sudjana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2011)
The research objectives were to discovered how’s Lumbricus rubellus and Organic mulching able to replenished soil physics characteristic of Inceptisol Karawang. It also been studied that soil loss to water erosion is able to be predicted by using these parameters. As a results, linearly Lumbricus and mulch were abled to reduce bulk density value, and also soil permeability. These research practices is one of tools to predict level of erosion. Moreover, Lumbricus and organic mulching are “eco-friendly” agent in a system of soil tillage-less.